MODEL PENDIDIKAN DAN PELATIHAN TENAGA KESEJAHTERAAN SOSIAL DI DAERAH ISTIMEWA YOGYAKARTA - Sugiyanto; Supartini (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
This research is entitled the model of education and training of social welfare workers (TKS) in the coordinating body for social welfare activities (BK3S) in the Special Region of Yogyakarta (DIY) which was held because of the mandate of Law Number 11 of 2009 and other accompanying regulations, as well as the limited human resources of TKS, in social welfare institutions (LKS). As a result of the problem of limited human resources, LKS is unable to provide services to the Social Welfare Service Needs (PPKS) according to LKS service standards and hinders the LKS accreditation process. The research approach used is descriptive qualitative. The research focus is on the model of TKS education and trainning, the inhibiting factors and the driving factors for TKS trainning. Informance was determined by purposive sampling technique as many as 8 informants. Data were collected through interviews, observation and literature study. To ensure the validation and reliability of the data, triangulated methods, sources, time and results, qualitative data analysis using the Creswell 2016 technique. The conclusion of the research shows that the TKS training model organized by BK3S DIY is effective in increasing the capacity of the Management and Managers of Social Welfare Institutions. So that the output of LKS has human resources according to the mandate of Law number 11 of 2009 concerning social welfare, and outcomes for LKS are met with accreditation requirements, the outcomes of trainning participants can take TKS certification because the trainning curriculum, time and teachers are in accordance with the trainning signs set by the social work science education bond, and the Indonesian professional social work association. Limitations of the study, this research needs to be continued by evaluating the first to fifth batch of trainning alumni and LKS stakeholders, if the results of the positive evaluation of the model held by BK3S DIY can be developed nationally.